IMPLEMENTATION OF CUSTOMER RELATIONSHIP MANAGEMENT BASED OF ARTIFICIAL INTELLIGENCE IN THE DHARMA BOOST MARKETING PROGRAM - cantika kusuma; Endy Gunanto Marsasi (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Dharma Mitra Abadi is a leader in the DIY and Central Java regions which uses the best branded tools, continues to maintain and develop the quality of its services. Committed with PT. Abbott with the best brand diagnostic tools, until appointed as the sole agent. PT. Dharma Mitra Abadi is a medical device company that utilizes direct marketing to promote its products. The company has implemented the Dharma Boost program, which utilizes digital media and e-commerce tools such as online electronic applications, websites, mobile applications, social media, animation, video, data visualization, and location-based services. This research aims to evaluate and improve the effectiveness of these existing programs within the company. The research method used is qualitative, including direct observation, in-depth interviews, collection of documentation, and analysis of company secondary data. The research is being conducted within the marketing division of the company. The goal is to help the company innovate and address any marketing challenges. By incorporating Artificial Intelligence into its Customer Relationship Management, PT. Dharma Mitra Abadi hopes to optimize its use of digital marketing.